Pharmacoeconomic evaluation in cost of illness in type 2 diabetes mellitus patients in a tertiary care hospital - Bagle, Tushar R.; Vare, Vijay A.; Nimgade, Alankar; Hire, Rohankumar C.; Sharma, Yogesh; Kshirsagar, Prasita (International Journal of Basic & Clinical Pharmacology, 2017)
Background: India is expected to bear the burden of world’s greatest increase of diabetes population. This burden needs to be considered in terms of costs. Methods: Cross-sectional study was done in type 2 diabetes mellitus 100 patients that attended Medicine OPD. Prior to enrollment Institutional Ethics Committee permission was taken. Written Informed consent was taken. Demographic information related to Education, Occupation and Income was taken down. Also Information related to diagnostic tests and medications were documented. Inclusion criterion were 18-70 years of either gender diagnosed by Physicians in OPD as type 2 diabetes, willing to participate and have followed in OPD for at least one year. The Exclusion criterion was Critically ill or unconscious patients and Pregnant women. Direct and indirect costs were calculated. Results: The average age was 56.31±10.50 years. The average fasting blood glucose was 120.65±22.70mg/dl. The average cost per month for investigations was 159.74±128.06. Annual visit to OPD was 13.06±7.35. Time loss per visit was 5.62±1.29 hours and of accompanying person was 6.55±3.87 hours. There were 2 from Lower and 63 from Upper Lower socioeconomic class. There were 41 patients having diabetic complications. The indirect cost was around 5838.51 and direct cost was around 19925. Total cost per annum per patient was around 32361.27 INR. Conclusions: There is need for strategies to reduce the cost burden. There is also needed to design financial systems for diabetes related nationwide health programs.